Dissecting light sensing and metabolic pathways on the millimeter scale in high-altitude modern stromatolites - Alonso-Reyes, Daniel Gonzalo; Galván, Fátima Silvina; Irazoqui, Jose Matias; Amadio, Ariel; Tschoeke, Diogo; Thompson, Fabiano; Albarracín, Virginia Helena; Farias, María Eugenia (Springer, 2023)
Modern non-lithifying stromatolites on the shore of the volcanic lake Socompa (SST) in the Puna are affected by several extreme conditions. The present study assesses for the first time light utilization and functional metabolic stratification of SST on a millimeter scale through shotgun metagenomics. In addition, a scanning-electron-microscopy approach was used to explore the community. The analysis on SST unveiled the profile of a photosynthetic mat, with cyanobacteria not directly exposed to light, but placed just below a high-UV-resistant community. Calvin–Benson and 3-hydroxypropinate cycles for carbon fixation were abundant in upper, oxic layers, while the Wood–Ljungdahl pathway was dominant in the deeper anoxic strata. The high abundance of genes for UV-screening and oxidant-quenching pigments and CPF (photoreactivation) in the UV-stressed layers could indicate that the zone itself works as a UV shield. There is a remarkable density of sequences associated with photoreceptors in the first two layers. Also, genetic evidence of photosynthesis split in eukaryotic (layer 1) and prokaryotic (layer 2). Photoheterotrophic bacteria, aerobic photoautotrophic bacteria, and anaerobic photoautotrophic bacteria coexist by selectively absorbing different parts of the light spectrum (blue, red, and IR respectively) at different positions of the mat. Genes for oxygen, nitrogen, and sulfur metabolism account for the microelectrode chemical data and pigment measurements performed in previous publications. We also provide here an explanation for the vertical microbial mobility within the SST described previously. Finally, our study points to SST as ideal modern analogues of ancient ST.